The Beneficial Effect of Spiritual Social Support on Depression and Quality of Life in Chronic Renal Failure Patients Undergoing Haemodialysis - Susanti; Bistara, Difran Nobel; Setiawan, Arif Helmi; Ikwan, Mochamad; Umamah, Faridah; Zahroh, Chilyatiz; Sham , Fatimah Binti; Nordin, Roswati Binti; Mustamu, Alva Cherry (Scripta Medica, 2025)
Background/Aim: Patients with chronic kidney disease (CKD) undergoing haemodialysis are at a high risk of depression and diminished standard of life due to the physical, emotional and social complexities of their condition. Spiritual social support has been suggested as a potential intervention to alleviate these psychological and quality-of-life challenges. Aim of this study was to examine the influence of spiritual social support on depressive symptoms and quality of life in CKD patients receiving dialysis treatment.Methods: The current investigation utilised a quasi-experimental approach with a pre- and post-test control group structure. Ninety-two patients from Rumah Sakit Islam Surabaya were separated into two groups: intervention (n = 46) versus control (n = 46). The therapy consisted of three sessions of spiritual social support, which focused prayer, spiritual guidance and emotional stabilisation. Depression was examined using the Beck Depression Inventory (BDI) and quality of life was determined using the Kidney Disease Quality of Life Short Form (KDQOL-SF). The data has been examined utilising paired t-tests, independent t-tests and multiple linear regression.Results: The intervention group demonstrated a major reduction in depression levels. (pre: 18.5 ± 4.3, post: 12.0 ± 3.5, p < 0.001) a considerable improvement in quality-of-life scores (pre: 55.2 ± 8.1, post: 68.5 ± 6.3, p < 0.001). In contrast, the control group showed no major alterations in either depression (p = 0.345) or quality of life (p = 0.982). Regression analysis demonstrated that spiritual social support significantly influenced both depression (B = -0.45, p < 0.001) and quality of life (B = 0.60, p < 0.001).Conclusion: This study emphasises the positive impact of spiritual social support on psychological wellness and quality of life in patients with CKD. The above findings indicate integrating spiritual care into treatment programs for dialysis patients. Spiritual social support diminishes depression and raises quality of life in those with CKD obtaining haemodialysis, hence adding to holistic treatment approaches.
Keywords: Renal insufficiency, chronic; Renal dialysis; Depression; Quality of life; Spiritual therapies